Review of the Chinese species of Gynnidomorpha Turner, 1916 (Lepidoptera: Tortricidae: Cochylini) - Sun, Yinghui; Li, Houhun (Zootaxa, 2013)
Ten species of Gynnidomorpha Turner, 1916 occur in China. Gynnidomorpha curviphalla, sp. nov., is described, and G. datetis (Diakonoff, 1984) is recorded from China for the first time. Images of adults and genitalia are provided, along with a key to all known Chinese species based on the male genitalia. A map showing the geographic distribution of the species is also provided.